PWE-043 Clinical inertia in coeliac disease. (17th June 2017) - Blanshard, R; Penny, H; Kurien, M; Naylor, G; Sanders, D
Abstract : Introduction: Clinicians' knowledge and practice may directly affect patients' diagnostic pathway. An Endomysial antibody (EMA) has a>90% positive predictive value for coeliac disease. Furthermore NICE have recommended that patients with suspected coeliac disease should have an endoscopy and biopsy within 6 weeks. This should serve to reduce the temptation by the patient to start a Gluten free diet (GFD). We aimed to determine GI Consultant practice by assessing their 'grading' for patients referred from primary care with a positive EMA. In addition, we sought to determine Gastroenterologists' views about coeliac disease. Method: Data regarding time to diagnostic endoscopy was collected from adult patients who had a positive EMA test in primary care from 2 centres (n=151). As a comparator cohort, we collected data regarding the time from symptom presentation in primary care to index endoscopy in adults referred with suspected IBD (n=92). In addition, an unselected cohort of Gastroenterology consultants and specialist registrars (n=50) completed a questionnaire regarding coeliac disease. Results: The median time from positive EMA identified in primary care to referral for diagnostic endoscopy was 23 (12-35) days; the time from referral to endoscopy was 55 (26-90) days. Overall, coeliac patients waited significantly longer from referral to endoscopy than patients who were diagnosed with IBD (34.5 [18-70] days; p=0.006). Overall time from EMA positive blood test to endoscopy was 78 (58-120) days. 32% (16) of Gastroenterologists failed to identify that coeliac disease was more prevalent in the adult population than IBD. 16% (8) of respondents felt that a diagnosis of coeliac disease does not significantly impact patient quality of life. 36% (18) felt that doctors were not required for the adequate management of coeliac disease. Conclusion: There are delays in diagnosis for patients with coeliac disease. This may impact treatment intensification and thus patient related outcomes. Our data suggest that provider-related beliefs may contribute to clinical inertia in this condition. We advocate enhancing both undergraduate and postgraduate training about coeliac disease to help reduce this effect. Disclosure of Interest: None Declared